Determinasi Pengungkapan Key Audit Matters pada Perusahaan Sektor Finansial yang Terdaftar di Bursa Efek Indonesia Tahun 2022 dan 2023 (Lembaga Pengembangan Kinerja Dosen, 2025)
Audit Standard 701 regarding Key Audit Matters (KAM) disclosure will be implemented in 2022. This standard sets additional responsibilities for auditors to present KAM that can increase transparency and communicative value in the independent auditor's report. This study aims to analyze the effect of the public accounting firm type, audit fees, audit committee size, and audit committee meeting frequency on KAM disclosure. The research sample consisted of 83 companies obtained by purposive sampling method from the population of financial companies listed on the Indonesia Stock Exchange in 2022 and 2023. Then, the data was analyzed using multiple linear regression analysis method. The results of the study found that the frequency of audit committee meetings had a significant positive effect, the type of public accounting firm had a significant negative effect while audit fees and audit committee size did not affect KAM disclosure.